APLIKASI CLUSTERING PENGEMBANGAN RESELLER ORDERBERDASARKAN KOTA - Indra Maulana Yusup Kusumah; Sutisna Senjaya; Dedy Apriyadi (LPPM STMIK Bandung, 2021)
At Tasshel Convection, resellers are individuals who buy and sell company products. The data on reseller sales orders at Tasshel Convection is steadily increasing. Additionally, the company utilizes a web-based sales system for processing reseller orders. Despite having resellers from various cities to market its products, the company still faces challenges in developing and boosting product sales. To address this issue, a system needs to be created that can classify reseller orders by city. This initiative, carried out at Tasshel Bandung Convection, aims to enhance sales by targeting cities with the most potential and opportunities for product sales. The strategy includes adding resellers or new outlets to ensure products reach more consumers, thereby increasing sales and enabling the company to compete more effectively with others. The objective of developing an application and analyzing reseller orders for Tasshel Convection in Bandung City is to use the K-Means method. This application will facilitate clustering reseller sales by city, making it easier to analyze reseller order grouping, and to determine and classify reseller orders based on city.